Guanine‐Stabilized Formamidinium Lead Iodide Perovskites. Issue 12 (3rd February 2020) - Hong, Li; Milić, Jovana V.; Ahlawat, Paramvir; Mladenović, Marko; Kubicki, Dominik J.; Jahanabkhshi, Farzaneh; Ren, Dan; Gélvez‐Rueda, María C.; Ruiz‐Preciado, Marco A.; Ummadisingu, Amita; Liu, Yuhang; Tian, Chengbo; et al.
Abstract: Formamidinium (FA) lead iodide perovskite materials feature promising photovoltaic performances and superior thermal stabilities. However, conversion of the perovskite α‐FAPbI3 phase to the thermodynamically stable yet photovoltaically inactive δ‐FAPbI3 phase compromises the photovoltaic performance. A strategy is presented to address this challenge by using low‐dimensional hybrid perovskite materials comprising guaninium (G) organic spacer layers that act as stabilizers of the three‐dimensional α‐FAPbI3 phase. The underlying mode of interaction at the atomic level is unraveled by means of solid‐state nuclear magnetic resonance spectroscopy, X‐ray crystallography, transmission electron microscopy, molecular dynamics simulations, and DFT calculations. Low‐dimensional‐phase‐containing hybrid FAPbI3 perovskite solar cells are obtained with improved performance and enhanced long‐term stability. Abstract : Guanine perovskites : Stabilization of the α‐FAPbI3 phase (FA=formamidinium) is realized by using guaninium (G) based G2 PbI4 low‐dimensional perovskites, forming heterostructures that lead to improved performances and stabilities of the corresponding solar cells. The structural properties are investigated to unravel the mode of action and set the path for using this approach in perovskite solar cell research.